2021
DOI: 10.2147/rmhp.s325312
|View full text |Cite
|
Sign up to set email alerts
|

Who should receive treatment? Healthcare professionals’ perspectives surrounding the medical management of patients with COVID-19

Abstract: Background:The COVID-19 pandemic has resulted in unprecedented challenges for healthcare systems worldwide. This pandemic is much more than a health crisis; it has also raised many ethical challenges. The large number of infected patients amid scarce resources has placed healthcare professionals in a critical situation in which they have to make difficult decisions about how to prioritize their patients. Therefore, the aim of this study is to explore the ethical challenges experienced and perceived by healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…This was consistent with other findings on the challenges practitioners face in balancing their commitments to patients with their commitments to their loved ones 55 56. Another study described participants’ accounts of moral uncertainty as they relate to medical intervention, triage and resource allocation especially in the absence of scientific evidence 57. Interestingly, a different study identified ethical challenges pertaining to the country’s robust public health response, where some participants expressed difficulty in coping with newfound restrictions but were ultimately supportive of these warranted measures 58.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This was consistent with other findings on the challenges practitioners face in balancing their commitments to patients with their commitments to their loved ones 55 56. Another study described participants’ accounts of moral uncertainty as they relate to medical intervention, triage and resource allocation especially in the absence of scientific evidence 57. Interestingly, a different study identified ethical challenges pertaining to the country’s robust public health response, where some participants expressed difficulty in coping with newfound restrictions but were ultimately supportive of these warranted measures 58.…”
Section: Discussionsupporting
confidence: 86%
“…55 56 Another study described participants' accounts of moral uncertainty as they relate to medical intervention, triage and resource allocation especially in the absence of scientific evidence. 57 Interestingly, a different study identified ethical challenges pertaining to the country's robust public health response, where some participants expressed difficulty in coping with newfound restrictions but were ultimately supportive of these warranted measures. 58 Indeed, the authors of this last study add their support in accordance with the principles of bioethics.…”
Section: Discussionmentioning
confidence: 99%